Penguatan Pendidikan Moral Siswa melalui Pelajaran Pendidikan Agama Islam dan Ekstrakurikuler di MTs NU Walisongo Sidoarjo - Arina Salamah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2020)
Moral Education is education to make human children moral or human. This means that moral education is education that does not teach about academics, but non-academics specifically about attitudes and how good everyday behavior. This paper is the result of field research entitled strengthening the moral education of students in following the eyes of Islamic and extracurricular learning in mts nu walisongo sidoarjo. issues discussed include how morale students in MTs. NU Walisongo Sidoarjo, How to strengthen moral education of students in MTs. NU Walisongo Sidoarjo And What are the supporting and inhibiting factors of the Student Morale Education Strengthening Program at MTs. NU Walisongo Sidoarjo To answer the above problems the authors use the case study method combined with field studies. This research uses qualitative research. Researchers use Emile Durkheims theory as quoted by George Ritzer and Douglas J. Goodman defines moral education is education that will be carried to the end of life. Education will determine when he becomes a useful human being, and will take him to heaven or hell later. The results of this study concluded that, the strengthening of students moral education was formed through positive programs that were quite simple and not burdensome for students and teachers, where those programs were able to form good character and achievements for students of MTs. Nu Sidoarjo.